Acylation of α-Chymotrypsin by Oxygen and Sulfur Esters of Specific Substrates: Kinetic Evidence for a Tetrahedral Intermediate - Hirohara, Hideo (1974)
The acylation step of the α-chymotrypsincatalyzed hydrolysis of N-acetyl-L (or DL)-tryptophan p-nitrophenyl, p-nitrothiophenyl, ethyl, and thiolethyl esters has been studied by the stopped-flow technique at 25°. The acylation rate constant, k(2), and the enzyme substrate dissociation constant, K(s), were directly determined at pH 4, 5, and 8. Steady-state kinetics were studied at pH 7. The k(2) values are nearly identical for oxygen esters and their sulfur counterparts, whereas the K(s) value of the ethyl ester is larger by an order of magnitude than those of the other three. The results strongly suggest that oxygen and thiol esters of these specific substrates are hydrolyzed via the same pathway, and furthermore that acylation consists of more than one step, the formation and breakdown of a tetrahedral intermediate, the former being rate-determining. Effects of leaving-group hydrophobicity on k(2) and K(s) are also discussed.